MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK MELALUI PERMAINAN ENGKLEK DI RA KURNIA PANAM - Yulia Astuti; Zulkifli N '; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to find out the improvement of 5-6-year old children gross motor ability at RA Kurnia Panam by using traditional game hopscotch. This research was a classroom action research which was conducted in two cycles. The instrument used was the observation sheet form. The total sample was 14 children that consist of 8 boys and 6 girls. Based on the analysis of the assessment process, there was an improvement in those two cycles.The research results were very satisfying because there were significant average scores improvement before the treatment from the first cycle to the second cycle. The improvement of the average scores was from 38,92 to 50,59 with the percentage 29,98 % and from 50,59% to 70,7% with the percentage 39,77 %. It can be concluded that the learning process by using traditional game have positive effects for children and it can improve the children motor ability.